Charlotte Walsh likes to win [large type] : a novel - Piazza, Jo (Wheeler Publishing, a part of Gale, a Cengage Company, 2018)
A searing, suspenseful story of political ambition, marriage, class, sexual politics, and infidelity, Charlotte Walsh Likes to Win is a glorious portrait of what it takes for a woman to run for national office in America today.